Afrocolombian Ethno- education: Concepts, obstacles, patriarchy and sexism, Apropos of the 20th anniversary of the General Law of Education 115 of 1994 - Meneses Copete, Yeison Arcadio (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper presents a reflection about the Afrocolombian Ethno-education, which is firstly set out from the perspective of a new concept, but an ancient practice; taking into consideration the historical-traditional and ethno-educative strategies used by afrodescendant communities, which, currently, lead to particular practices, beliefs, ideas, knowledge, and particular worldviews. Secondly, it is proposed a debate from the popular and institutional constructions of the afrocolombian social movement on Ethno-education for considering difficulties and possibilities over the last 20 years. In this sense, the debate approaches the idea of an endogenous and exogenous ethno-education by mainly discussing teachers training and the role of ethno-education in relation to Racism, Racial Discrimination and the demand for other schools. Finally, it suggests a conceptual look of ethno-education against racism and sexism. It includes gender equality and sexual diversity as confronting proposals towards the transformation of the national educative system, in order to highlight and place human diversity, especially, the Afrocolombian diversity in the discourse of ethno-education.